Awareness and utilization of female condoms among street youths in Ibadan, an urban setting in South-West Nigeria (2019)
Introduction: female condom awareness and use have been poorly documented in sub-Saharan region especially among street youths. This study assessed its awareness and use among street youths. Methods: a cross-sectional study was conducted among 964 youths between ages 15 to 24 years old using questionnaires to elicit information. Univariate and multivariate analysis were conducted at 5% level of significance. Results: more than half (69.9%) were males and between 20-25 years of age (61.2%). More than three-quarter (81.0%) had initiated sexual activity. Almost half (47.9%) of the respondents have heard about female condoms however only 16.8% have ever seen while 4.3% have actually ever used a female condom. Age, education, current sexual activity and experience of rape attempt were predictors of female condom awareness. Conclusion: awareness of female condom was a significant predictor of utilization of female condoms. There is therefore a need for proper awareness and education on the effectiveness of female condoms.